Análise crítica do sistema de franquias no Brasil - Proença, Maria Cristina de Araújo (1997)
This study aims at investigate the current situation o f franchising system in Brazil and give a better comprehension of the reasons why franchisees defected from their franchising networks. Firstly, a theoretical framework is presented. Afterwards, the results of a exploratory research based on Case Studies methodology on eleven ex-franchisees from different networks. The goal is to identify the factors that caused insatisfaction with the franchise and the main reasons for defection. Lastly, the limitations and the contributions of the study, as well as some sugestions for future studies.